Battle for dominant design: A decision-making model - Esteban Fernández Vázquez; Sandra Valle (European Research on Management and Business Economics (ERMBE), 2019)
This paper synthesizes, analyses and organizes the factors that can be decisive in a battle for a dominant design. The result is the construction of a rational decision-making model, where the relevant factors are grouped into three blocks – market, technology, and complementary assets. First, the firm must decide on the strategic manoeuvres that it is going to deploy to be able to capture the market that it has created or invaded. Second, technologically, it must decide whether to compete with its design made public or private, open or closed. Finally, it must plan its access to complementary assets without which it would be impossible to exploit the new design in a mainstream market. The proposed model is integrative in character and practical in approach, and it helps in forming a strategy and decision-making in the usual design wars today. It is aimed to contribute to a literature in which the analysis of factors is usually done in a fragmented form, without the systematic approach that would facilitate rational and dynamic decision making.
Keywords: 650; Battle for the standard; Dominant design; Mainstream market; New design